Pengaruh Arus Globalisasi Terhadap Pembentukan Karakter Peserta Didik Sekolah Dasar dalam Mendukung SDG 4 Pendidikan Berkualitas - Priyono Tri Febrianto; Izzatul Maulidha Rama Dhani; Silvi Milata Saliana; Nurul Hayati; Amalia Nur Vikrani (Continuous Education: Journal of Science and Research, 2026)
Globalization and technological advancement have increasingly influenced the lives of elementary school students, particularly in the process of character formation. On one hand, globalization provides broader access to information and learning resources; on the other hand, it also creates challenges such as behavioral changes, declining discipline and responsibility, and increasing individualistic tendencies. This issue is important to examine in supporting the achievement of SDG 4 (Quality Education). This study aims to analyze the influence of globalization on the character formation of elementary school students and its relation to achieving quality education. The study employed a descriptive qualitative approach using a literature review method. Data were collected from relevant national and international journal articles and analyzed through content analysis to identify patterns and key findings across previous studies. The findings indicate that globalization has both positive and negative impacts on students’ character development. Positive impacts include easier access to information, broader knowledge, increased creativity, and greater learning independence. However, negative impacts were also identified, including decreased discipline, empathy, and social interaction, as well as increased dependence on digital technology. The study concludes that character education plays a strategic role in minimizing the negative effects of globalization. The implication of this study is that schools, teachers, and parents need to integrate character education and digital literacy continuously to support the achievement of quality education.